Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kepuasan Kerja dengan Komitmen Organisasi sebagai Variabel Intervening Generasi Z di Indonesia - Fitriani Fitriani; Yulyanti Fahruna; Syahbandi Syahbandi; Maria Christiana Iman Kalis; Endah Mayasari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study will investigate organizational commitment as a mediating variable in Generation Z employees in Indonesia to improve understanding of the relationship between work motivation, work discipline, and job satisfaction. This study examined a sample of 255 employees from Generation Z. Respondents were selected using a purposive sampling method. Research information was collected using an online questionnaire distributed through Google Forms with a quantitative method. The Structural Equation Modeling (SEM) approach and SmartPLS 4 software were used for data analysis to assess and examine the relationship between variables in the proposed research model. According to the research findings, work motivation significantly increases organizational commitment, but does not have a statistically significant direct impact on job satisfaction. On the other hand, work discipline greatly affects organizational commitment and job satisfaction. In addition, organizational commitment has a positive and significant impact on job satisfaction and acts as an important mediator between work motivation, discipline, and job satisfaction.